2015
DOI: 10.1016/j.yexcr.2015.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Cell source-dependent in vivo immunosuppressive properties of mesenchymal stem cells derived from the bone marrow and synovial fluid of minipigs

Abstract: The in vitro differentiation and immunosuppressive capacity of mesenchymal stem cells (MSCs) derived from synovial fluid (SF-MSCs) and bone marrow extract (BM-MSCs) in an isogenic background of minipigs were comparatively analyzed in a collagen-induced arthritis (CIA) mouse model of rheumatoid arthritis (RA). The proliferation capacity and expression of pluripotent transcription factors (Oct3/4 and Sox2) were significantly (P<0.05) higher in SF-MSCs than in BM-MSCs. The differentiation capacity of SF-MSCs into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
65
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 56 publications
4
65
0
1
Order By: Relevance
“…Much of the initial MSC research was focused on bone marrow MSC (BM-MSC) populations; however, it is now well established that MSCs are present in most tissues and body fluids. Despite similarities in isolation protocols, MSCs derived from different tissues demonstrate significant variation in their ability to adopt specific phenotypes, synthesize functional extracellular matrices [3][4][5] and modulate immunological and inflammatory pathways during tissue repair [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Much of the initial MSC research was focused on bone marrow MSC (BM-MSC) populations; however, it is now well established that MSCs are present in most tissues and body fluids. Despite similarities in isolation protocols, MSCs derived from different tissues demonstrate significant variation in their ability to adopt specific phenotypes, synthesize functional extracellular matrices [3][4][5] and modulate immunological and inflammatory pathways during tissue repair [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Their study also demonstrated that MSCs could inhibit activation of T cells and induce Tregs expansion in RA [22]. Another study on synovial fluid (SF)-MSCs showed that the immunosuppressive properties of these MSCs in CIA mice were associated with increased levels of the anti-inflammatory cytokine IL-10, and decreased levels of the proinflammatory cytokine IL-1β [23].…”
Section: Introductionmentioning
confidence: 96%
“…Mesenchymal stem cells (MSCs), derived from mesodermal cell lineages with self‐renewing capacities and multipotential differentiation, have profound therapeutic potential in many diseases, such as tissue engineering and regeneration, autoimmune disease, and myocardial infarction (Jungebluth et al, ; Lee et al, ; Wang et al, ). Moreover, MSCs showed low immunogenicity and transplantation of allogeneic MSCs would not cause immune rejections.…”
Section: Introductionmentioning
confidence: 99%